2018
DOI: 10.1016/j.physa.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in tumor growth VI: Epithelial–Mesenchymal transition

Abstract: Highlights• Cancer as an open, complex, self-organizing nonlinear dynamic system.• The epithelial-mesenchymal transition appears as ""first order"" phase transition.• EMT exhibit a Shilnikov"s chaos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…A rather standard approach is to answer specific questions at each scale of interest by formulating dedicated models. These can be based on Statistical Mechanics [4], Kinetic Theories [5,6,7,8,9], and Continuum Mechanics [10,11] (and references therein), depending on whether the given problem involves the molecular, cellular, or the tissue scale. One of the main challenges, however, is to understand the complexes of phenomena that contribute to initiate the sprouting of a tumour, and to bridge across the physical scales at which they occur.…”
Section: Introductionmentioning
confidence: 99%
“…A rather standard approach is to answer specific questions at each scale of interest by formulating dedicated models. These can be based on Statistical Mechanics [4], Kinetic Theories [5,6,7,8,9], and Continuum Mechanics [10,11] (and references therein), depending on whether the given problem involves the molecular, cellular, or the tissue scale. One of the main challenges, however, is to understand the complexes of phenomena that contribute to initiate the sprouting of a tumour, and to bridge across the physical scales at which they occur.…”
Section: Introductionmentioning
confidence: 99%
“…Most tumors release millions of cells into the bloodstream, but only a small number of metastatic lesions develop, indicating the inefficiency of the metastasis process [37] , this means weakness of metastasis, despite the fact that, as has been shown in previous work [16] , metastasis is a highly robust process. In the extravasation process, tumor cells undergo changes to improve adhesion; this process is closely related to the populations of the immune system and to the action of the new microenvironment [37] .…”
mentioning
confidence: 73%
“…In previous works we have shown that the growth of cancer studied through cell population models and interactions with immune cells, is a complex process. Control in such process could be precisely in that interaction with the immune system; this could be the source of its complexity and its adaptability [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [31] we have shown that the rate of entropy production is a Lyapunov function, in fact we extended this formalism to the development of cancer [32,33,34,35,36,37]. Thus, we have the entropy production per unit time meets the necessary and sufficient conditions for Lyapunov function [30], such that , that allows us to affirm that the rate of entropy production is a Lyapunov function.…”
Section: Thermodynamics Frameworkmentioning
confidence: 86%